1986
DOI: 10.1007/bf00441858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pituitary-thyroidal axis in newborns undergoing exchange transfusion

Abstract: To evaluate whether the hypothyroxinaemia, previously noted in hyperbilirubinaemic newborns immediately after exchange transfusion for Rh or AB0 incompatibility, was due to impairment in the secretion of thyroid stimulating hormone (TSH) by the pituitary, we studied the thyroid hormone response to thyrotropin releasing hormone (TRH) and compared this response to that seen in a control population of healthy neonates. All infants studied responded with a brisk TSH increase; 30 min after TRH injection the mean TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…4,5 Lanes revealed that concentrations of T4 and TSH decrease significantly after exchange transfusion and remained significantly below pre-exchange values 30 hr later. 6 We…”
Section: Effects Of Exchange Transfusion On Neonatal Thyroid Functionmentioning
confidence: 99%
“…4,5 Lanes revealed that concentrations of T4 and TSH decrease significantly after exchange transfusion and remained significantly below pre-exchange values 30 hr later. 6 We…”
Section: Effects Of Exchange Transfusion On Neonatal Thyroid Functionmentioning
confidence: 99%